Compliance to instructions on complete denture wear and care of patients in the UPCD prosthodontic section a descriptive study - Jacinto, Martin Francis K.; Natividad, Patricia Mae A.; Atienza, Charlie
Introduction. In complete denture service, patient compliance to their dentist's instructions on the proper way of wearing and using the dentures, as well as their maintenance and care, plays a critical role in the treatment's success or failure. clinicians give either reinforced instruction (verbal instructions with a written list) or verbal instructions only. The difference in the method and the content of the post installation instructions may affect overall patient compliance to instruction.
Methods. Eleven patients and nine clinicians participated in the study. An oral examination and denture evaluation was administered on patients to observe the following: (1) discomfort/pain, (2) presence of sores, (3) denture damage and (4) denture plaque percentage. Next was an interview, composed of two parts: (1) compliance hindrances identification and (2) guidelines followed by patients on proper denture care. Findings were rated as positive or negative. Interviewing the clinician was done to determine the method and content of instructions to patients.
Results: Patients given reinforced instructions exhibited a lower average plaque percentage (6.85%) and a higher percentage of positive answers (80%) as compared to 17.62% and 57.69% respectively, among patients who did not receive reinforced instructions. The percentage of compliant patients were as follows: 18.18% on proper overnight storage, 36.36% on proper chewing, 45.45% on proper diet and eating technique, 90.90% on proper denture cleaning and 63.64% on proper storage of dentures. Patients below 50 years old and patients who did not receive instructions from outside sources showed better compliance. 72.73% patients and 77.78% of clinicians believed that the best way of educating was through reinforced instructions however only two of the nine clinicians gave reinforced instructions. Most clinicians did not include instructions on proper chewing technique and speech.
Conclusion. The percentage of compliant patients varied depending on the specific instruction given. The percentage of compliant patients were as follows: 18.18% on proper overnight storage, 36.36% on proper chewing, 45.45% on proper diet and eating technique, 90.90% on proper denture cleaning and 63.64% on proper storage of dentures. The findings showed that compliance to denture care guidelines of the subjects could still have been improved.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Patient compliance; Complete denturse